The Directive Speech Acts in Hamka’s Menunggu Beduk Berbunyi: A Study of Commands and Influence - Desmiana Fitriani; Yulia Sri Hartati; Upit Yulianti DN (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2024)
This research explores the use of directive speech acts in Hamka’s novel Menunggu Beduk Berbunyi. The main focus is to analyze the forms of directive speech acts found within the narrative, particularly examining how these speech acts reflect the social and interpersonal dynamics of the characters. Using a qualitative descriptive analysis method, the study categorizes 40 instances of directive speech acts, sourced from the 2017 edition of the novel. The analysis reveals five key forms of directive speech: ordering, commanding, advising, requesting, and recommending. Among these, commanding speech acts dominate the novel, with 17 instances identified. Examples include phrases such as